The Presentation of potential data for Micro, Small and Medium Enterprises (MSME) in the Food Sector at vilage office website - Salfiana, Salfiana; Hermansyah, Sam; Mannu, Ahmad; Nurwidah, Andi (MALLOMO: Journal of Community Service, 2020)
The title of this paper is the presentation of potential data for Micro, Small and Medium Enterprises (MSME) in the Food Sector at vilage office website. The purpose of this paper is the existence of MSME data in food as a source of information for development needs, especially in the food sector. The implementation method consists of preparation and briefing, data collection and data collection to the Village Website. Food MSME data presented on the Website consists of Pipang MSME profiles, the current market and the stabilization of food prices in the market. The Community Service Program 1 UMS Rappang is expected to benefit the community. By providing MSME data on this website, it is expected to be information for MSME development strategies in particular and the Environment Kampung Pisang in general.